Dilatative Uropathy as a Manifestation of Neurohypophyseal Diabetes Insipidus due to a Novel Mutation in the Arginine Vasopressin-Neurophysin-II Gene - Lindenthal, V.; Mainberger, A.; Morris-Rosendahl, D. J.; Löning, L.; Mayer, W.; Müller, H. L. (Klinische Pädiatrie, 2013)
Polydypsia and polyuria are frequent symptoms in patients with sellar masses caused by neurohypophyseal diabetes insipidus. Autosomal dominant familial neurohypophyseal diabetes insipidus (adFNDI), a disorder caused by mutations in the arginine vasopressin (AVP) neurophysin II (NPII) gene, should be considered as a rare differential diagnosis. A delayed diagnosis bears the risk of life-threatening electrolyte imbalances and permanent urinary tract damage, leading to impaired quality of life.We present a Caucasian kindred of at least 4 generations with FNDI.Clinical histories, endocrine parameters, and results of molecular analyses of the AVP gene are presented with a review of the literature on diabetes insipidus (DI) related urinary tract dilatation.Polyuria and polydipsia were only reported based on explicit and thorough interrogation after more than 4 years of clinical follow-up. A novel heterozygous mutation in the AVP gene was found in all examined symptomatic subjects (c.1-33_c.4del37nt). A literature review revealed that non-obstructive hydronephrosis (NOH) is a rare but known complication of DI.Since increased fluid intake is often a typical familial pattern in adFNDI, it is frequently missed as being pathologic in affected patients, therefore a detailed clinical history of drinking volumes is of critical importance. AVP gene testing is an important component in the confirmation of the diagnosis. Otherwise unexplainable NOH should lead to further investigations and evaluation of rare diseases like FNDI.
Keywords: diabetes insipidus; hydronephrosis; AVP neurophysin-II gene mutation; clinical history; AVP gene testing; pediatric neurooncology